The Effect of External Cold and Vibration on Infiltration-Induced Pain in Children: A Randomized Clinical Trial - Faghihian, Reihaneh; Esmaeili, Mona; Asadi, Hossein; Nikbakht, Mohammad Hossein; Shadmanfar, Fateme; Jafarzadeh, Mehdi (International journal of dentistry, 2022)
Introduction. Children’s fear of and anxiety about dental treatments are important problems in maintaining health. The anesthetic injection is the main cause of dental fear. One of the methods to reduce the infiltration-induced pain is to use external cold or vibration using the gate control system. Various devices have been used to apply cold and vibration, including the BUZZY device (BUZZY Company, Arizona). Studies have shown contradictory results for the effectiveness of cold and vibration. This study aimed to investigate the effect of cold and vibration versus cold alone on maxillary infiltration-induced pain and stress. Methods. Thirty children aged 6–12 years who required profound restoration of deciduous or permanent first molars were recruited in this randomized double-blind clinical trial. The anesthetic gel and BUZZY device were used in half of the children’s jaws, and the anesthetic gel and the cold alone were used in the other half of the jaws. To measure stress from the heart rate, the Wong–Baker scale was used as the subjective scale, and the face, legs, activity, cry, consolability (FLACC) scale was used as the objective scale. Results. The FLACC score was significantly lower in the BUZZY group than in the cold-alone group, but the Wong–Baker scale and heart rate did not show a significant difference between the two groups. Conclusions. The BUZZY device can be effective in reducing infiltration-induced dental pain.